BA71ΔCD2: a New Recombinant Live Attenuated African Swine Fever Virus with Cross-Protective Capabilities - Monteagudo, Paula L. (J Virol, 2017)
African swine fever is a highly contagious viral disease of mandatory declaration to the World Organization for Animal Health (OIE). The lack of available vaccines makes its control difficult; thus, African swine fever virus (ASFV) represents a major threat to the swine industry. Inactivated vaccines do not confer solid protection against ASFV. Conversely, live attenuated viruses (LAV), either naturally isolated or obtained by genetic manipulation, have demonstrated reliable protection against homologous ASFV strains, although little or no protection has been demonstrated against heterologous viruses. Safety concerns are a major issue for the use of ASFV attenuated vaccine candidates and have hampered their implementation in the field so far. While trying to develop safer and efficient ASFV vaccines, we found that the deletion of the viral CD2v (EP402R) gene highly attenuated the virulent BA71 strain in vivo. Inoculation of pigs with the deletion mutant virus BA71ΔCD2 conferred protection not only against lethal challenge with the parental BA71 but also against the heterologous E75 (both genotype I strains). The protection induced was dose dependent, and the cross-protection observed in vivo correlated with the ability of BA71ΔCD2 to induce specific CD8(+) T cells capable of recognizing both BA71 and E75 viruses in vitro. Interestingly, 100% of the pigs immunized with BA71ΔCD2 also survived lethal challenge with Georgia 2007/1, the genotype II strain of ASFV currently circulating in continental Europe. These results open new avenues to design ASFV cross-protective vaccines, essential to fight ASFV in areas where the virus is endemic and where multiple viruses are circulating. IMPORTANCE African swine fever virus (ASFV) remains enzootic in most countries of Sub-Saharan Africa, today representing a major threat for the development of their swine industry. The uncontrolled presence of ASFV has favored its periodic exportation to other countries, the last event being in Georgia in 2007. Since then, ASFV has spread toward neighboring countries, reaching the European Union's east border in 2014. The lack of available vaccines against ASFV makes its control difficult; so far, only live attenuated viruses have demonstrated solid protection against homologous experimental challenges, but they have failed at inducing solid cross-protective immunity against heterologous viruses. Here we describe a new LAV candidate with unique cross-protective abilities: BA71ΔCD2. Inoculation of BA71ΔCD2 protected pigs not only against experimental challenge with BA71, the virulent parental strain, but also against heterologous viruses, including Georgia 2007/1, the genotype II strain of ASFV currently circulating in Eastern Europe.